Evaluación ambiental y socioeconómica a la extracción de orquídeas en el cantón quijos, mediante la aplicación de la matriz causa efecto de leopold para proponer un plan de manejo ambiental en la hostería quinde huayco - Aguilera Maldonado, Jorge Andrés (2016)
Orchid populations are severely threatened in the research area of native forests of Quijos, due to causes that alter that environment as logging, advancing agricultural frontier, selective logging, in addition to the impact that opening highways of second and third order as well as some land reform programs that allowed communal settlements in native forest areas with the following research topic entitled "Evaluación Ambiental y Socioeconómica a la Extracción de Orquideas en el cantón Quijos mediante la Aplicación de la Matriz Causa Efecto de Leopold para proponer un Plan de Manejo Ambiental en la Hostería Quinde Huayco" for developing area studies and biotic and abiotic factore identified.; an environmental social survey and environmental impact assessment wing pair Leopold matrix cause-effect and a proposed environmental management plan was implemented; resulting in that 57% of respondents agree with the extraction of orchids and 83% acceptance of orchid growing in gardens. The positive environmental impacts assessment found that employment sources and reaches +59 8 positive and according to the method of interaction cause-effect conditions flora obtained the negative impact more significativocon -54 and 10 negative conditions of reversible character; to preserve, control and mitigate such impacts environmental management plan which is structured with environmental programs that will be available to the authorities of the Ministry of Environment, and the owner of the inn Quinde Huayco is proposed.